Mauritinus seferi Bondar, 1960: bionomy, description of immature stages and redescription of adult (Coleoptera, Curculionidae) - Márcio Luís Leitão Barbosa; Roberta de Melo Valente (Revista Brasileira de Entomologia, 2003)
Mature larvae of Mauritinus seferi Bondar, 1960 were collected in the mesocarp of murity palm (Mauritia flexuosa Linnaeus), in the State of Pará, Brazil. Larvae were reared to pupa and adults in the laboratory. Mature larva and pupa are described and adult redescribed. Adult and immature are illustrated for the first time. Observations about bionomy are included and discussed.